Interactive Models in University Teaching: Application in Pharmacy Education - Tomevska Ilievska, Elizabeta; Tonic Ribarska, J.; Trajkovic Jolevska, S.; Ancevska Netkovska, K.; Tofovikj Kjamilova, Marija (My University, 2019)
The research deals with the constant seeking of academic staff to improve the quality of higher education. The issue in defining the most successful approach resides in monitoring and assessment and the ability to reach the highest levels of student participation and ownership of learning. The third generations of universities or the universities of tomorrow strongly vouch for a participant-centered environment (PCL) in all fields of education, making the approach cross-disciplinary. The issue has been explained upon the backdrop of the undergraduate education in pharmacy, as a domain where the concept of active and lifelong learning is crucial through interdisciplinarity, as a contemporary image of the pharmacist in the 21st century. A program that has been exemplified is the credit transfer system introduced in Macedonian Universities in the attempt to delve deeper into student constant participation and enable teaching staff constant monitoring. The drive for such a research is to talk about programs that work and to single them out in terms of functionality thus propose a proactive approach towards interactive teaching and learning. The finish line represents creating a classroom where both teaching staff and learners are mutual stakeholders, thus learning will represent an exchange.
Keywords: interactive models of teaching, PCL, undergraduate, pharmacy, lifelong learning, interdisciplinarity, credit transfer system